Proliferation Activity in Canine Gastrointestinal Lymphoma. (November 2021) - Wolfesberger, Birgitt; Burger, Stefanie; Kummer, Stefan; Walter, Ingrid; Tichy, Alexander; Klinger, Sabine; Alton, Klemens; Burgener, Iwan A.; Liehmann, Lea; Hammer, Sabine E.; Rütgen, Barbara C.; Fuchs-Baumgartinger, Andrea
Summary: Gastrointestinal lymphomas are uncommon in dogs and little is known about their distinct subtypes or proliferation rate. The aim of this study was to stratify 33 canine gastrointestinal lymphoma samples according to the latest World Health Organization classification and to determine the Ki67 proliferation index by manual counting, digital image analysis and visual estimation. The Ki67 index was then correlated with subtype, immunophenotype, mitotic index, grade and tumour location. The mitotic index correlated positively with the Ki67 index. A significantly higher number of Ki67-positive cells was found in enteropathy-associated T-cell lymphoma type I and in diffuse large B-cell lymphoma compared with enteropathy-associated T-cell lymphoma type II. There was also a significant difference in Ki67 immunolabelled cells between grade 1 and grade 2 lymphomas. Moderate agreement was found between the Ki67 index as obtained by manual counting and visual estimation, but there was strong agreement between manual counting and digital image analysis. The user-friendly digital imaging system used in this study could have potential for future determination of the Ki67 index in lymphoid neoplasms.